The Great Railroad Race : The Diary of Libby West - Gregory, Kristiana (New York Scholastic Inc, 1999)
As the daughter of a newspaper reporter, fourteen-year-old Libby keeps a diary account of the exciting events surrounding her during the building of the railroad in the West in 1868.
Includes Maps and illustrations.
Keywords: Frontier and Pioneer life; Diaries